2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319681
|View full text |Cite
|
Sign up to set email alerts
|

Far-field effect in unipolar electrograms revisited: High-density mapping of atrial fibrillation in humans

Abstract: Unipolar electrogram can detect local as well as remote electrical activity of the heart. Information on how the amplitude and morphology of the recorded signal changes with the distance from the source tissue undergoing depolarization can help to better understand unipolar electrograms fractionation and provide insights into the passive conduction properties of the atrial tissue. Ten second unipolar atrial fibrillation (AF) electrograms were recorded using high-density electrode array from the posterior left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Podziemski et al determined this relationship in 3D atrial tissue. The investigators used activation wave fronts that traveled along a line of conduction block . In this way, they were able to measure the amplitude of electrograms at several distances from activated tissue distal from the line of block.…”
Section: Unipolar Recording Modementioning
confidence: 99%
See 2 more Smart Citations
“…Podziemski et al determined this relationship in 3D atrial tissue. The investigators used activation wave fronts that traveled along a line of conduction block . In this way, they were able to measure the amplitude of electrograms at several distances from activated tissue distal from the line of block.…”
Section: Unipolar Recording Modementioning
confidence: 99%
“…The investigators used activation wave fronts that traveled along a line of conduction block. 4 In this way, they were able to measure the amplitude of electrograms at several distances from activated tissue distal from the line of block. The authors fitted the data to an exponential function, but it can be shown that the amplitude-distance curve they composed fits well with the inverse of the distance to the power of 2 for large distances.…”
Section: Change In Signal Amplitude With Distance In 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude of the unipolar EGM is dependent on local activation and a far‐field component which decreases by the power of 2 with distance as demonstrated by Podziemski et al 10 in three‐dimensional atrial tissue, although the exact relationship may change depending on the source of far‐field activation (i.e., focal/planar/rotational). Both components will also be reduced in the presence of myopathic structural remodeling or regional conduction block which decreases the number of depolarized myocytes under the recording electrode and its field of view.…”
Section: Discussionmentioning
confidence: 83%
“…The decay function property is in line with the results from a surgical study in patients with paroxysmal and persistent AF. 14 Based on the experimental data of 10 sec unipolar EGMs from a high-density electrode array and a computer simulation, they observed a decay to 50% of the source unipolar EGM within 1.5 mm to 2.1 mm function. This is in the same range for the ring electrode in our study between 2 mm and 4 mm distance (140% to 70% for amplitude and 180% to 90% for the slope).…”
Section: Discussionmentioning
confidence: 99%